2011
DOI: 10.2134/agronj2011.0018
|View full text |Cite
|
Sign up to set email alerts
|

Seed, Oil, and Protein Yields of Canola under Combinations of Irrigation and Nitrogen Application

Abstract: Canola (Brassica napus L.), an important oilseed crop in Iran, is intensively managed with high inputs of N and irrigation water. Understanding N and water use characteristics of canola will help improve N and water use effi ciency (WUE) and reduce production costs. Here, the eff ects of irrigation levels (IL 1 , 750; IL 2 , 450; and IL 3 , 300 mm water ha -1 ) and N rates (NR 1 , 0; NR 2 , 40; NR 3 , 80; NR 4 , 120; and NR 5 , 160 kg N ha -1 ) on canola production are evaluated during 2006 and 2007 growing se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 27 publications
5
8
0
Order By: Relevance
“…With reduced nitrogen (N3 and N4) and irrigation application rates (D2 and D3), TDM decreased and the lowest values was observed under D3N4 condition. These findings are in line with those of Gan et al (2008), Ali et al (2009), Hamzei (2011 and Hamzei et al (2012). They observed that increasing nitrogen levels increase the biological yield of the crop.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…With reduced nitrogen (N3 and N4) and irrigation application rates (D2 and D3), TDM decreased and the lowest values was observed under D3N4 condition. These findings are in line with those of Gan et al (2008), Ali et al (2009), Hamzei (2011 and Hamzei et al (2012). They observed that increasing nitrogen levels increase the biological yield of the crop.…”
Section: Discussionsupporting
confidence: 90%
“…In fact, N deficiency reduces vegetative and reproductive growth with a final impact on the yield (Tewolde & Fernandez, 1997). Higher rates of N may shift the balance between vegetative and reproductive growth toward excessive vegetative development, thus delaying crop maturity and reducing final yield (Howard et al, 2001;Hamzei, 2011). Water deficit remarkably decreases the nitrogen translocation ratio derived from soil and adversely affects the contributions of nitrogen in various vegetative organs to grain nitrogen (Xu et al, 2006;Hamzei, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…correlated with the nitrogen application. Indeed, these results are in agreement with those found by Ali et al, (2009), Massignam et al, (2011) and Hamzei (2011), who observed that increased nitrogen improved the biological yield of crops. Similarly, MacDonald (2002) investigated the effect of different nitrogen doses on the yield of several varieties of durum wheat, and observed that TDM at the anthesis stage increased significantly with increasing nitrogen rate.…”
Section: IVsupporting
confidence: 93%
“…With 20 cm water applied, Pavlista (2012) reported a yield of 1600 kg/ha which is near the amount reported here for LI treatment receiving 25-26 cm of water (Table 4). Hamzei (2011), and Hamzei and Soltani (2012) reported that 45 cm of applied water was needed to achieve a yield of 2565 kg/ha in Iran and a reduction of applied water to 30 cm reduced yield by greater than half. Majnooni-Heris (2014) recently reported a yield of 1790 kg/ha with 50 cm of applied water also in Iran.…”
Section: Yieldmentioning
confidence: 99%